2013
DOI: 10.1002/fuce.201200010
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Linking of Sulfonated Poly(ether ether ketone) by Thermal Treatment: How Does the Reaction Occur?

Abstract: The cross-link reaction between macromolecular chains of sulfonated poly(ether ether ketone) (SPEEK) by thermal treatment above 150 degrees C in presence of dimethylsulfoxide (DMSO) is investigated by various techniques, including elemental analysis, acid-base titration, infrared spectroscopy, water uptake (WU) measurements, and thermogravimetry. The conditions of thermal treatment are analyzed. The cross-linking reaction occurs in at least three more or less activated and deactivated positions with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 51 publications
(52 reference statements)
0
32
0
Order By: Relevance
“…Previous studies on SPEEK decomposition only reported SO 2 release in a unimodal peak between 200 and 400 8C (a temperature shift of some tens of degrees could be the result of differences in heating rate), although not all studies include an evolved-gas analysis up to a temperature of 500 8C. [13,15,17,27] Scheme 1 summarizes the two possible routes for SO x loss from the material: protodesulfonation or ipso substitution. If a sulfone (R-SO 2 -R) bridge is formed by ipso substitution, this sulfone bridge can in turn decompose at higher temperatures, yielding the release of a second SO x species.…”
Section: Conversion Of Extinction Coefficient To Absorption Coefficientmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies on SPEEK decomposition only reported SO 2 release in a unimodal peak between 200 and 400 8C (a temperature shift of some tens of degrees could be the result of differences in heating rate), although not all studies include an evolved-gas analysis up to a temperature of 500 8C. [13,15,17,27] Scheme 1 summarizes the two possible routes for SO x loss from the material: protodesulfonation or ipso substitution. If a sulfone (R-SO 2 -R) bridge is formed by ipso substitution, this sulfone bridge can in turn decompose at higher temperatures, yielding the release of a second SO x species.…”
Section: Conversion Of Extinction Coefficient To Absorption Coefficientmentioning
confidence: 99%
“…[28] Upon ipso substitution, SO 2 release would be expected. It has to be noted that the ipso substitution reaction was found to depend strongly on the presence of traces of solvent: it was found to occur in the presence of DMSO, [13,15] but not with NMP, DMAc, or DMF. [29] A third possible reaction, H-substitution, results in cross-linking as well, but will not cause SO 2 release.…”
Section: Conversion Of Extinction Coefficient To Absorption Coefficientmentioning
confidence: 99%
See 2 more Smart Citations
“…After cooling to room temperature, the resulting membranes were peeled off and thermally treated at 180 °C for 3, 10, and 24 h. The mechanism of cross-linking was studied and described in references 30,31 .…”
Section: Speek 28 29mentioning
confidence: 99%